Semiotic Analysis of the Meaning of Islamic Faith in Dialogue And Mise Yes Movie Scene "Sarong Fight" - Haikal, Muhammad Adrian; Akbar, Nadzmi; Rani, Samsul (Interdisciplinary Explorations in Research Journal, 2024)
Semiotics is a science or analytical methods to study systems, rules, and conventions that allow signs to have meaning. The research entitled Analysis Semiotics Meaning Faith Islam in Dialog And Misc Yes Scene Film "Fight Sarong" analyzing the meaning of Islamic belief from the signs in the scene in the film "Tarung" Sarong" work Archie Hekagery. This research is a qualitative research with a qualitative descriptive method, namely by looking for signs of Islamic belief in the components of the film "Tarung Sarung" in particular dialog And mise en scene . Analysis data done with describe findings with theory- related theories. The selected data samples were analyzed using Roland's semiosis theory. Barthes. The results of this study show that the film "Tarung Sarung" contains meaning. ideology about creed Islam. Theory semiotics Roland Barthes capable to dismantle signs found in the film Tarung Sarung through dialogue and mise en scene as a sign Work to know meaning  Islamic faith in the scene.